“Market Day” Learning Media in Implementing Contextual Learning in Elementary Schools - Putri Ageng Yoga; Kukuh Andri Aka; Bagus Amirul Mukmin; Intan Mekar Sari (Universitas Pendidikan Ganesha, 2026)
Mathematics learning still tends to be abstract in elementary school so that it makes it difficult for students to understand the concept of arithmetic operations in a meaningful way. This condition shows the need for learning media innovation that is able to associate the material with the student's real-life context. This research aims to analyze the validity, practicality, and effectiveness of the